PENGARUH IMPLEMENTASI TEKNIK KLARIFIKASI NILAI (TKN) DAN MOTIVASI BERPRESTASI TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN PKn PADA SISWA KELAS V SD DI GUGUS 1 MENDOYO KABUPATEN JEMBRANA – BALI - I Komang Winata (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2017)
The major aim of this study was to test the effect of Values ClarivicationTechnique (VCT) upon learning achievement as viewed from the achievementmotivation of the fifth graders of Group 1 Elementary Schools in Mendoyo inBali. This study was an experimental research which selected the existing fifthgraders of Group 1 Mendoyo as the sample. The sample was determined byrandom sampling. This study involved three variables, namely, ValuesClarivication Technique (VCT) as the independent variable and learningachievement in Civic Education as the dependent variable and achievementmotivation as the moderating variable. The data were collected by learning achievement in Civic Educationand questionnaire on achievement motivation. All of the data in this study wereanalyzed by two-way ANOVA which was preceded by the testing of thenormality and homogeneity of the variance of each of the cell in this study. The results showed that : (1) there was a significant difference inlearning achievement in Civic Education between the group of students who studied through Values Clarivication Technique (VCT) learning model and thegroup who studied through conventional learning model, (2) for the group ofstudents with high and low achievement motivation there was a significantdifference in learning achievement in Civic Education between the group ofstudents who studied through Values Clarivication Technique (VCT) learningmodel and the group who studied through conventional learning model, and (3)there was a significant interaction effect between Values ClarivicationTechnique (VCT) learning model and learning achievement upon learningachievement in Elementary Civic Education teaching.